G610(P) Readiness for the future: young person experience and life skills project. (May 2019) - Parish, EJ; Hothi, D; Carter, C; Childs, L; Simpson, S
Abstract : Aims: Adolescence is a time of great opportunity as young people develop their personal identity and cultivate future career ideas. Often the Young People (YP) we care for in hospital settings miss out on key educational opportunities while receiving treatment, including career planning and advice. We wanted to run a co-created programme to meet the needs of this group, recognising the impact of health on employment goals and opportunities. With the help of local businesses, we devised a series of life skills days and a 'career festival'. Methods: During 2017 we ran a pilot of Life Skills Days. These half-day sessions included a networking icebreaker, CV writing exercise, mock interviews and Q and A with staff in a corporate environment. Those attending were encouraged to come independently, without parents. In case of any medical needs, attendees were accompanied by clinical staff. Briefing documents about the experience of YP were shared with businesses in advance. We formed a working group of staff, YP representatives, Charity and Education to develop a Careers Festival with stalls, drop-in sessions and talks from former patients and employees about working with long term conditions and disability. Results: 3 life skills events were held. 28 YP attended (aged 15–24 years). All attendees agreed the day was useful to them and all said they would recommend it to others. Attendees rated the experience an average of 9.5 out of 10. The most popular sessions were interview practice and CV writing. Qualitative feedback highlighted the need for specialist advice on how to address health needs in the workplace and at interview. The career festival in 2018 was attended by 40 YP with similarly positive qualitative and quantitative feedback. Most YP lived in our region, but some travelled considerable distances from out-of-area. Conclusion: Part of the continuous care of YP is supporting their development to fulfil their potential. YP enjoyed the events and some benefit from subsequent mentoring and work experience. We are conscious that travel costs could prove to be prohibitive and are working with our charity and Young People's Forum to improve the accessibility and sustainability of the programme. Acknowledgments Morgan Stanley team and GOSH Working Group for GOSH Teens Career Festival.